Single-supply readout interfacing circuit for extended-gate field effect transistor pH sensing system with data logger / Mohamad Faisal Azlan - Azlan, Mohamad Faisal (2015)
A single supply readout interfacing circuit (ROIC) for an extended gate field effect transistor (EGFET) pH sensor has been developed. The ROIC is used to capture the changes in the potential between a reference electrode and an extended-gate coated with sensing membrane. The potential changes are due to the differences in the ionic activities in different pH buffer solutions. The extended gate is connected to the gate of a commercialized MOSFET. Due to the small current and instability of reading produced by the sensing membrane, the ROIC is needed to obtain and stabilize the generated voltage. A constant voltage constant current (CVCC) circuit was applied in the ROIC with a drainsource voltage of 0.50 V and operates in the linear region at 330 uA drain current, using a single supply. The output of the ROIC is fed to a microcontroller to display the pH level and data logger to allow drift measurement for the sensor characterization. Based on the previous ROIC design and system, a dual supply operational amplifier is used and will produce negative output which is not compatible with microcontroller interfacing thus need extra hardware to be interfaced with microcontroller. Also, the previously proposed system can only do limited sensor characterizations and there is a need to have a system that can support in-depth sensor characterizations. Therefore, the aim of this research is to design a single supply ROIC for Extended-Gate Field Effect Transistor and to equip the system with data logger and design a graphical user interface (GUI) application using Visual Basic software for in-depth sensor characterizations. The developed circuit and system proved that it was able to capture the voltage changes and was able to be applied in measuring pH buffer solutions for pH 4, 7, and 10. The data from the data logger was controlled by a GUI developed using Visual Basic and drift and hysteresis measurements were successfully carried out.